2012
DOI: 10.5392/jkca.2012.12.06.390
|View full text |Cite
|
Sign up to set email alerts
|

Aanalysis on the Competency of Nursing Students' Basic Nursing Skills

Abstract: As medical practices and procedures become more specialized and information technology develops in clinical settings, health organizations need medical personnel with special skills, knowledge and competency. But the lack of practical experience in clinical settings may impair competency in basic nursing skills among nursing students. This study used a cross-sectional survey to analyze factors related to nursing competency among nursing students in order to establish effective teaching methods to increase the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Learning satisfaction refers to the degree of satisfaction with students' attitude, degree of preparation by professors, progress and content of lectures, and degree of study assessment [12]. Participating in self-directed classes after self-directed learning through prior practice will increase confidence and satisfaction with satisfaction with the classes.…”
Section: Effect Of Prior Learning Methods On Nursing Students' Practicmentioning
confidence: 99%
“…Learning satisfaction refers to the degree of satisfaction with students' attitude, degree of preparation by professors, progress and content of lectures, and degree of study assessment [12]. Participating in self-directed classes after self-directed learning through prior practice will increase confidence and satisfaction with satisfaction with the classes.…”
Section: Effect Of Prior Learning Methods On Nursing Students' Practicmentioning
confidence: 99%
“…When comparing the learning satisfaction scores for overall learning and the practice method before and after the practice within the groups, significant increases were found in the experimental group for both items, whereas the control group did not exhibit any significant changes for both items. As learning satisfaction was an influential factor for skill competency (Song, Kim, & Yu, 2012), it was thought to be a preferred outcome due to the fact that it significantly improved in the experimental group through the intervention. It is assumed that the significant increase of learning satisfaction in the experimental group occurred because the smartphone video recording practice facilitated students' self-directed learning in the course of the practice, including their performance, evaluation of the practice process, and repeated learning.…”
Section: Conclusion Discussion and Recommendationmentioning
confidence: 99%
“…Nursing education institutions have recognized the importance of fundamental nursing practice and have made great efforts to increase skills, accuracy, and proficiency. However, ensuring one-on-one learning between the instructor and learner is difficult, and students' basic nursing competencies have not been satisfactory (Chae & Ha, 2016;Song, Kim, & Yu, 2012). As a result, improving competency is deemed necessary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, previous studies have researched the factors affecting satisfaction with the Jeong et al / Effect of Learning Core Fundamental 2 / 10 practice and educational effects in an effort to increase the effectiveness of the practical education. These studies have identified learning satisfaction and self-efficacy as the factors affecting the effectiveness of practical education (Park & Lee, 2008;Song, Kim, & Yu, 2012). These results suggest the necessity for developing an effective educational intervention that increases the proficiency of nursing skills while engaging learners.…”
Section: Introductionmentioning
confidence: 99%